(untitled) (Research, Society and Development, 2024)
Objective: To map in the literature the scientific production on developed and/or validated technologies that aim to contribute to the effectiveness of the process of compulsory notification of diseases in the hospital context. Methodology: Scoping review protocol, conducted by the Joanna Briggs Institute (JBI) methodology, guided by the review question prepared according to the conceptual model of the PCC mnemonic – (Population, Concept, Context). Articles, theses and dissertations will be included from searches in the following databases: Medical Literature Analysis and Retrieval System Online (Medline/PubMed), Latin American and Caribbean Literature in Health Sciences (LILACS)/Virtual Health Library (VHL ), Cumulative Index to Nursing and Allied Health (CINAHL), Web of Science (WOS), Scopus, Excerpta Medica Database (Embase), as well as in the gray literature. The data will be extracted and organized in Excel software through a spreadsheet to be developed by the author. Protocol registered with the Open Science Framework (OSF): 10.17605/OSF.IO/DKR4F. Results: The results will be presented in a flowchart, highlighting the search and inclusion/exclusion process of publications, followed by discussion, preparation of tables and illustrative figures. Conclusion: Protocol with the purpose of systematizing and describing the methodological steps for carrying out a scoping review that aims to identify studies in the literature that address technologies with the aim of contributing to the implementation of the process of compulsory notification of diseases in the hospital context.